Development and evaluation of an aerodynamic model for a novel vertical axis wind turbine concept - Shires, Andrew (MDPI, 2013)
There has been a resurgence of interest in the development of vertical axis wind turbines which have several inherent attributes that offer some advantages for offshore operations, particularly their scalability and low over-turning moments with better accessibility to drivetrain components. This paper describes an aerodynamic performance model for vertical axis wind turbines specifically developed for the design of a novel offshore V-shaped rotor with multiple aerodynamic surfaces. The model is based on the Double-Multiple Streamtube method and includes a number of developments for alternative complex rotor shapes. The paper compares predicted results with measured field data for five different turbines with both curved and straight blades and rated powers in the range 100-500 kW. Based on these comparisons, the paper proposes modifications to the Gormont dynamic stall model that gives improved predictions of rotor power for the turbines considered.
Keywords: vertical axis wind turbine (VAWT); blade element momentum (BEM); aerodynamic model; dynamic stall